Effect of extraction method on antioxidant activity and phytochemical content of purple okra extract supplements - Ni’maturrohmi Miftahul; Damayanthi Evy; Rimbawan Rimbawan (BIO Web of Conferences)
This study analyzed the effects of extraction methods on the antioxidant activity and phytocemical content of purple okra extract supplements. The extraction methods used in the preparation of the supplements were maceration and digestion. The purple okra extract supplement showed antioxidant capacity expressed as % inhibition of 99.73±0.17% and 83.46±0.90%, with an AEAC of 12.50±0.32 and 9.43±0.17 mg AEAC g⁻¹. The antioxidant activity, expressed as IC50, was measured at 233.01±61.69 and 391.05±8.90 ppm, indicating weak antioxidant activity. The purple okra extract supplement showed total phenols of 72.80±18.55 and 62.65±22.85 mg GAE g⁻¹, and total flavonoid content of 90.73±6.11 and 75.62±7.06 mg QE g⁻¹. Based on the statistical analysis using an independent t-test, it was found that the extraction method significantly affected the parameters of antioxidant activity and capacity, as well as total flavonoid content. By elucidating the influence of extraction methods on the activity, capacity, and phytochemical content of purple okra extract supplements, this study enhances our understanding of the importance of using appropriate extraction methods to maximize the extraction of active compounds. Future research is expected to optimize extraction methods, exploring solvent combinations, conducting in vivo studies on the therapeutic potential of purple okra, and examining its molecular mechanisms.